Narasi para Korban sebagai Basis Konstruksi Identitas Sosial Kristen yang Terbuka - Astrid Bonik Lusi (Indonesian Journal of Theology, 2016)
Narratives of the violence victims can contribute to an open Christian social identity. This article contains violence narratives of women in East Timor and narratives about First Peter community. There are two reasons behind the selection of those narratives. First, both narratives are violence narratives from the victims’ perspective and trauma narratives. Second, those different narratives show the link between narratives in everyday life and narratives that come from the Bible. The purpose of the selection of these narratives is to give a deep understanding of violence and trauma and their contribution to the construction of an open Christian social identity.